2017
DOI: 10.1515/folmed-2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

Lethality among Patients with HIV/AIDS Monitored in the Clinic of Infectious Diseases in St George University Hospital, Plovdiv, 2010–2014

Abstract: Background: The introduction of complex antiretroviral therapy has resulted in signifi cant decrease in the mortality rate of HIV positive patients, but it still remains unacceptably high, especially in some groups of patients. Aim: To investigate the death rate in patients with HIV/AIDS, lethality and mortality in co-infection, and the most common causes and predictors of fatal outcome, focused on early diagnosis and appropriate therapy. Materials and methods: The study included 53 deceased patients with HIV/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Similar to our study, common coexistence of tuberculosis and AIDS was also reported in this study, and the fact that deaths were due to AIDS-related causes and importance of early ART use were emphasized. 14 Studies from other developing countries also report higher mortality rates among hospitalized PLHIV (up to 38% versus 2.6%). Mortality has been linked with advanced disease stages, low CD4 cell count, presence of opportunistic infections, and lack of resources for patient care.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to our study, common coexistence of tuberculosis and AIDS was also reported in this study, and the fact that deaths were due to AIDS-related causes and importance of early ART use were emphasized. 14 Studies from other developing countries also report higher mortality rates among hospitalized PLHIV (up to 38% versus 2.6%). Mortality has been linked with advanced disease stages, low CD4 cell count, presence of opportunistic infections, and lack of resources for patient care.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to our study, common coexistence of tuberculosis and AIDS was also reported in this study, and the fact that deaths were due to AIDS-related causes and importance of early ART use were emphasized. 14…”
Section: Discussionmentioning
confidence: 99%